2010
DOI: 10.1002/jbmr.268
|View full text |Cite
|
Sign up to set email alerts
|

Rab27a and Rab27b are involved in stimulation-dependent RANKL release from secretory lysosomes in osteoblastic cells

Abstract: The quantity of the receptor activator of NF-kB ligand (RANKL) expressed at the cell surface of osteoblastic cells is an important factor regulating osteoclast activation. Previously, RANKL was found to be localized to secretory lysosomes in osteoblastic cells and to translocate to the cell surface in response to stimulation with RANK-Fc-conjugated beads. However, the in vivo significance of stimulation-dependent RANKL release has not been elucidated. In this study we show that small GTPases Rab27a and Rab27b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…Suppression of Rab27A or RAb27B by RNA interference causes markedly reduced secretion of RANKL in murine osteoblastic cell line ST2 cells41. These results also suggest that Rab27deficiency in osteoblasts results in reduced OCL activation.…”
Section: Discussionmentioning
confidence: 57%
“…Suppression of Rab27A or RAb27B by RNA interference causes markedly reduced secretion of RANKL in murine osteoblastic cell line ST2 cells41. These results also suggest that Rab27deficiency in osteoblasts results in reduced OCL activation.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous report, the researchers found that Rab27a-deficient osteoclasts showed a markedly impaired bone resorption activity, indicating the important role of Rab27a in maintaining the normal functions of osteoclasts [35,36]. They also showed that depletion of Rab27a results in abnormal phenotypes in osteoclasts.…”
Section: Discussionmentioning
confidence: 98%
“…Lysosomal vesicles transport RANKL molecules to the cell membrane [8,9], a process that involves lysosomal molecules such as Rab27 and Vps33; however, the mechanism of RANKL-lv fusion to the cell membrane is unknown. We suggest that membrane depolarization is the first trigger for vesicle fusion in RANKLiT.…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid hormone (PTH) and 1α,25-dihydroxyvitamin D 3 (VD 3 ) are osteogenic factors in bone remodeling and also major regulators of osteoclastogenesis [4,5], promoting osteoclast differentiation by increasing RANKL mRNA expression [6,7]. Previous reports have suggested that RANKLiT is lysosome-dependent and regulated by lysosomal molecules, including those of the Rab protein family [8,9]. Although the transport route has been partly described, an outstanding question is how RANKL lysosomal vesicles (RANKL-lvs) fuse to the cell membrane.…”
Section: Introductionmentioning
confidence: 99%